The E3 ligase C-CBL inhibits cancer cell migration by neddylating the proto-oncogene c-Src. Issue 41 (11th October 2018) - Lee, Gun-Woo; Park, Jun; Park, Sung; Seo, Jieun; Shin, Seung-Hyun; Park, Jong-Wan; Kim, Sang; Watanabe, Masatoshi; Chun, Yang-Sook
Abstract Neddylation is a cellular process that covalently conjugates substrate proteins with the small ubiquitin-like molecule NEDD8. As neddylation is required for fast turnover of proteins in proliferating cancer cells, the neddylation process is currently regarded as a potential target for cancer therapy. However, little is known about the role of neddylation in cancer invasion and metastasis. Unexpectedly, we here found that the neddylation blockade stimulates migration of lung cancer and glioblastoma cells. Mechanistically, C-CBL acts as the E3 ligase for neddylation of the proto-oncogene c-Src. After neddylation, c-Src is poly-ubiquitinated and degraded through the proteasome, which inhibits the PI3K–AKT pathway responsible for cell migration. In human lung cancer tissues, the downregulation of C-CBL was associated with c-Src/AKT, cancer metastasis, and poor survival in patients. Therefore, C-CBL is likely to play a tumor suppressive role by antagonizing a robust oncogenic signaling driven by c-Src. This study provides new insight about the role of neddylation in cancer metastasis. It also implies that the metastasis risk should be carefully evaluated before the clinical application of neddylation inhibitors as anticancer regimens.